Fabrication of a Molecularly Imprinted Polymer Adsorbent for Pipette Tip Micro Solid-phase Extraction of Levofloxacin from Aqueous Samples Prior to its Spectrophotometric Determination - Hashemi, Sayyed H.; Kaykhaii, Massoud; Keikha, Ahmad Jamali; Jangizahi, Jasem (Current Analytical Chemistry, 2023)
Aims: The main goal of this research was to find a simple, selective, sensitive and rapid protocol for the detection of traces of levofloxacin (Lev) in seawater, pills, urine, and human plasma samples by using a novel sorbent made of molecularly imprinted polymer (MIP) for its pipette-tip micro-solid phase extraction (PT-μSPE), followed by spectrophotometry. Parameters affecting the method were evaluated employing one-variable-at-a-time, Box-Behnken design (BBD) and central composite design (CCD) techniques, and results were compared together.Background: Lev, the active L-isomer isolated from racemic of loxacin, is a fluoroquinolone (FQ) antibiotic that is widely in use for curing infectious diseases due to its high activity against a large spectrum of both Gram-positive and Gram-negative bacteria. If it enters the environment, such as seawater, due to low degradation, it can remain there for the long term. Besides water, since Lev cannot be metabolized completely in the body, a selective and sensitive protocol for the analysis of Lev in biological fluids is necessary for physiological pharmacokinetics and clinical diagnosis.Objective: The objective was to find a fast, accurate and sensitive method for the determination of Lev in different sample matrices. This method should be very economical as well.Methods: This technique is based on using molecularly imprinted polymer adsorbent for pipette tip micro solid-phase extraction of Lev prior to its spectrophotometric detection.Results: The limit of detection of the developed protocol was 0.1 μg L-1, and its linear range was 1.0- 1,000.0 μg L-1 (R2=0.9934). The total time of analysis, including microextraction, was less than 10 min and for the analysis, a sample volume of 14 mL was adequate. 2.0 mg of the sorbent was sufficient for the extraction, and the sorbent could be reused for 4 times without loss in its extraction performance. For the spiked real samples at three levels, recoveries were in the range of 97.4% to 99.5%, with relative standard deviations better than 4.7%.Conclusion: The proposed protocol has advantages, including the simplicity of sorbent preparation and operation, consumption of a low amount of solvent and sorbent, which is in consistency with green chemistry, and high enrichment factor. In addition, it can be applied in samples with different matrices, has low analysis time (10 min), and uses inexpensive instruments.
Keywords: Levofloxacin